Catalogue : foster and partners. (Munich ;New York : Prestel Publishing, 2008)
Introduction - Norman Foster
Includes index.
Keywords: Architecture, Modern -- 20th century -- Catalogues; Mimarlık, Modern -- 20. yüzyıl -- Kataloglar